Estudo descritivo dos instrumentos utilizados por escolas médicas para avaliação dos estágios de internato pela perpectiva dos seus alunos: enfoque sobre a dimensão ética - Santos, Maria Fernanda dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
There is a growing demand for improvements in medical education in both technical and humanistic domains. The internship is a crucial period for the acquisition and development of skills by medical students. Efforts to understand how medical schools assess this important period of training may point out directions for improvement in medical education with implications for Public Health. Hence we aimed to analyze the instruments used by medical schools to evaluate the internship rotations from the point of view of their students. Our main hypothesis was that many instruments do not incorporate questions directed at the assessment of ethical conflicts occurring during that period. We conducted a cross-sectional study based on documentation analysis of the instruments used by Brazilian medical schools for evaluation of the internship rotations by their own students. We randomly selected 121 Brazilian medical schools. We excluded medical schools that still did not have students enrolled in any internship rotation as of the first semester of 2014. Two independent researchers examined the assessment instruments obtained and extracted standardized information for each instrument. Any disagreements between the reviewers will be solved through the assessment of a third researcher. Of the 121 institutions contacted, 46 agreed to participate in the survey. Among these, 23 stated that they some formal instrument for evaluation of the internship rotations by their students. Only 12 medical schools had instruments that addressed the ethical dimension in some way. In most cases the ethical issues examined were related to the attitude of preceptors. None of the instruments addressed the ethical issues related to the healthcare. Only two instruments questioned the students about negative ethical experiences and conflicts during the rotations and only one sought to find positive ethical experiences. We argue that assessment instruments based on the ...

Há uma demanda crescente por melhorias na formação médica tanto em aspectos técnicos como humanísticos. O internato se configura como um período central à aquisição e desenvolvimento de habilidades para os estudantes de medicina. Compreender a forma como as escolas médicas avaliam este importante período de formação pode apontar melhorias no ensino médico com repercussões sobre a Saúde Coletiva. Tivemos como objetivo analisar os instrumentos utilizados por escolas médicas para avaliar os estágios de internato por seus alunos. A hipótese principal é a de que muitos instrumentos não incorporam questões destinadas à avaliação de conflitos éticos durante o internato. Estudo seccional baseado na análise documental dos instrumentos utilizados por escolas médicas brasileiras para avaliação dos estágios de internato por seus alunos. Foram selecionadas aleatoriamente 121 escolas médicas brasileiras públicas ou privadas de quaisquer regiões do país. Foram excluídas escolas médicas que ainda não possuíam alunos cursando estágios de internato durante o primeiro semestre de 2014. Dois pesquisadores examinaram os instrumentos de avaliação obtidos e extraíram informações padronizadas de cada instrumento de forma independente. Quaisquer divergências entre os investigadores foram dirimidas por intermédio de um terceiro pesquisador. Das 121 instituições contatadas, 46 aceitaram participar na pesquisa, entre essas, 23 afirmaram que adotavam algum instrumento formal para avaliação dos estágios de internato por seus alunos. Apenas 12 escolas possuíam instrumentos que abordavam de alguma forma a dimensão ética. Na maioria dos casos as questões éticas examinadas se relacionavam à atitude dos preceptores quanto aos alunos. Nenhum dos instrumentos abordou a questão ética relacionada à equipe em suas relações de maneira geral, com o paciente ou com os alunos. Somente dois instrumentos questionavam os alunos...
Descriptive of the instruments used by medical schools to evaluate the rotations from the point od viee of their oen students : focus the ethical dimension
Keywords: Educação médica; Ética médica; Curriculos - Avaliação; Estagios; Medical education; Medical ethics